Dynamic modelling of inter‐relationship between tourism, energy consumption, CO2 emissions and economic growth in South Asia. (24th November 2020) - Selvanathan, Eliyathamby A.; Jayasinghe, Maneka; Selvanathan, Saroja
Abstract: Tourism is an important economic driver and plays a critical role in the economic development of South Asian countries. However, tourism also brings about some inevitable consequences on the environmental quality of these countries. Using the Autoregressive Distributed Lags, Vector Error‐Correction Model and Panel frameworks, we investigate the inter‐relationships between tourism, energy consumption, CO2 emissions and gross domestic product (GDP) in South Asia, using data for the period 1990–2014. We find that, in the long‐run, tourism positively contributes to GDP, CO2 emissions and to the demand for energy; an increase in GDP improves tourism; and an increase in CO2 levels is not a deterrent for tourists to visit South Asia.